Standardizing the Approach to Evidence-Based Upper Limb Rehabilitation after Stroke. Issue 5 (September 2013) - McDonnell, Michelle N.; Hillier, Susan L.; Esterman, Adrian J.
Abstract : Background andPurpose: To describe the development of a clinical algorithm to enable standardized intervention prescription and progression for upper limb rehabilitation post stroke.Methods: We developed a standardized clinical algorithm that involved assessment of 18 critical impairments of upper limb function and application of task-specific exercises appropriate to the level of impairment. These tasks were consistent with recent evidence-based guidelines. We tested the feasibility of the algorithm with 20 participants recently discharged from inpatient rehabilitation following stroke who received outpatient therapy according to the clinical algorithm. Participants' abilities were regularly re-evaluated and task difficulty progressed. Outcomes were assessed at the level of impairment (Action Research Arm Test, Fugl-Meyer Assessment) and activity (Motor Activity Log).Results: All participants attended the 9 sessions of training over the 3-week intervention period (100% compliance). No adverse events were reported. There were significant improvements in all outcome measures ( P < .01).Conclusions: This evidence-based upper limb clinical algorithm provides a framework for standardizing task-specific training following stroke based on the assessment of functioning of the individual following stroke in day-to-day life. This approach is appropriate for patients with different functional levels and may be used to standardize individual or group self-directed practice sessions or to standardize the intervention and progressions in experimental studies.